Code Switching Analysis In Efl Classroom Interaction Of Collage Student At IAIN Palangka Raya: A Sociolinguistic Study - Lusi Tri Utami; Maria Arina Luardini; Natalina Asi (Innovative: Journal Of Social Science Research, 2023)
This research aims to analyze the types and functions of code-switching that are used by teachers and students in EFL classroom interaction at IAIN Palangka Raya. The instrument of this research are observation, interview and documentation. The observation is conducted 3 times while interview was done to English lecturer and some students of class management to know the use of code switching in EFL classroom. The result shows that the teacher mostly used code-switching especially in explaining material to students. There are three types of code-switching based on Poplack theory which was used by the lecturer; tag switching, intrasentential switching and intersentential switching. Meanwhile, there are three functions of lecturer code-switching accomplished based on Sert. They were topic switch, affective function, and repetitive function. Besides, there are two functions of students code-switching accomplished. These functions are equivalence and reiteration.